Optimization of Boron Doped TiO2 as an Efficient Visible Light-Driven Photocatalyst for Organic Dye Degradation With High Reusability - Niu, Pingping; Wu, Guanghui; Chen, Pinghua; Zheng, Huitao; Cao, Qun; Jiang, Hualin (Frontiers in Chemistry, 2020)
No visible light activity is the bottle neck for wide application of TiO2. In this study, B was doped into TiO2 to prepare B-TiO2 photocatalyst, and its photocatalytic performance under visible light was investigated in details. SEM and TEM were used to study the morphology of B-TiO2; XRD was used to investigate the crystal characteristics of B-TiO2. Other techniques such as electronchemical impedance spectroscopy, photoluminescence, photocurrent response and UV-vis diffuse-reflectance spectra were applied to study the physicochemical properties of B-TiO2. The important active species involved in the photocatalytic process were carefully investigated to study the photocatalytic degradation mechanism, and the reusability of B-TiO2 was evaluated. The results indicate that B-TiO2 has high photocatalytic degradation ability towards rhodamine B under visible light irradiation, and can be effectively reused in 5 cycles. It is a highly potential photocatalyst to cope with dye pollution problems.